A Misdiagnosed Case of Endoleak Type-III Caused by Inadvertent Bilateral Limb Insertion in the Same Limb Gate of the Ovation Endograft - Georgakarakos, Efstratios; Koutsoumpelis, Andreas; Kostoglou, Panagiotis; Tasopoulou, Kalliopi-Maria; Argyriou, Christos (AORTA, 2022)
We describe an infrequent case of endoleak Type-III due to an unrecognized, inadvertent bilateral limb deployment into the same limb gate of the Ovation aortic endograft, accompanied by thrombosis and acute ischemia. The following computed tomography angiography revealed the open limb gate with the characteristic of radio-opaque polymer in the sealing rings. Intraoperative angiographies via the brachial route identified the open limb gate and facilitated the successful use of an occluding plug to manage the Type-III endoleak.
Keywords: endoleak; Ovation; endovascular aneurysm repair; Amplatz; occluding plug